GENDER, POLITIK DAN AGAMA - Dendi Sutarto (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2017)
Muhammadiyah is the largest religious social movement in Indonesia, based in Yogyakarta, Yogyakarta. The organization was founded on 8 Dhu al-Hijjah 1330 H or November 18, 1912 in Yogyakarta by KHAhmad Dahlan, the movement known as the Islamic purification movement